The coating of FeB, FeTi, FeW powders on AISI 430 stainless steel by PTA - Teker, T.; Karatas, S.; Yilmaz, S. O. (Natl Inst Optoelectronics, 2013)
In-situ synthesized TiB2, Fe2B reinforced Fe based coating was fabricated on an AISI 430 steel substrate by plasma transfer arc process (PTA) with FeB, FeTi, FeW powders. The effects of the process parameters on the coating were investigated experimentally. The surfaces were subsequently characterized by SEM, EDS and XRD to differentiate the effect of coating parameters on the microstructure. Primary ferrite (alpha) phase dendrites and complex TiB2, Fe2B borides around the dendrites were detected on the subsurface microstructure. The experimental results show that the distribution of boron and titanium is not homogeneous on either the coated surface or interface microstructures. The difference in hardness of the microstructures is specifically attributed to the type of borides.
Keywords: Microanalysis; Intermetallic; Plasma transferred arc; Hardening